Switzerland : Financial Sector Assessment Program; Technical Note-Macrofinancial Analysis and Macroprudential Policy. (IMF Staff Country Reports; Country Report ;, 2019)
Financial Sector Assessment Program; Technical Note-Macrofinancial Analysis and Macroprudential Policy.